Correlation of the Sperm Quality Index with ATP Utilization, Gas Exchange and Ionic Balance of Broiler Breeder Semen - Parker, H.M.; McDaniel, C.D. (International Journal of Poultry Science, 2007)
The Sperm Quality Index (SQI) is capable of predicting semen quality when semen is diluted 10-fold prior to analysis; yet when semen is diluted, changes in motility, gas exchange, Adenosine Triphosphate (ATP) and ion content occur. Therefore, the objectives of this research were to determine if the SQI could be a predictor of ATP, gas and ion content of semen and to determine if O2 and ATP content of semen could be used as predictors of seminal ion content when ejaculates are diluted 10-fold. Prior to semen analysis, ejaculates from 70 Ross males were diluted 10-fold using 0.85% saline and immediately analyzed to determine each ejaculate`s SQI as well as ATP, pH, O2, CO2, Na+, K+, Ca2+ and Cl- content. There was a positive correlation between the SQI and ATP present per sperm (r = 0.70, p<0.0001). However, the coefficients for the SQI with concentrations of O2, Ca2+, Na+ and Cl- present per sperm were negative (r = -0.70, -0.49, -0.51 and -0.53, respectively). The coefficient for the concentration of O2 per sperm with ATP per sperm was negative (r = -0.41) yet the coefficients for CO2, Ca2+, Na+, K+ and Cl- were positive (r = 0.30, 0.74, 0.77, 0.50 and 0.77, respectively). In conclusion, the SQI and O2 present per sperm can predict ATP and ion content in broiler breeder semen samples diluted 10-fold.